421 DIFFERENCES IN SUBJECTIVE AND OBJECTIVE SEXUAL FUNCTION BETWEEN HISPANIC AND NON-HISPANIC WOMEN. (1st January 2006) - Garcia, M.; Zuckerbraun, E.; Bhasin, S.; Berman, J.; Friedman, T. C.
Abstract : Objective: Recent studies have suggested that female sexual dysfunction may be has high as 40% in the United States and yet very few studies have examined sexual dysfunction in Hispanic women. Our previous studies suggested that low testosterone levels may be associated with both subjective and objective sexual dysfunction in hypopituitary women. Are there differences in testosterone levels, subjective and objective measures of sexual function between Hispanic and non-Hispanic females? Method: Subjective sexual function was assessed by the Female Sexual Function Index (FSFI) and the Female Sexual Distress Scale (FSDS) on 15 Hispanic and 10 non-Hispanic women. Total testosterone levels were measured. Objective sexual function measurements were by duplex Doppler ultrasound to assess clitoral blood flow before and after sexual stimulation. Medoc's GenitoSensory Analyzer-3000 was used to assess quantitative somatosensory thresholds of vibratory sensation. Results: Hispanic women did have a larger BMI that was statistically significant (29.05 ± 4.32 vs 24.30 ± 4.86, p = .0115). Hispanic women did have lower total testosterone levels but the results were not statistically significant (24.02 ± 1.25 ng/dL vs 37.75 ± 24.76 ng/dL, p = .3487). The Female Sexual Function Index (FSFI) suggested no statistically significant differences between Hispanic and non-Hispanic women scores on desire, satisfaction, orgasm, arousal, lubrication, and pain. On the Female Sexual Distress Scale, Hispanic women had more personal sexual distress than non-Hispanic women as suggested by a higher score (5.33 ± 6.66 vs 0.50 ± 1.22); however, these results were not statistically significant ( p = .0952). On the objective tests, Hispanic women had less vaginal sensitivity than non-Hispanic patients as suggested by measurements of vaginal vibratory thresholds (4.25 ± 1.66 vs 2.03 ± 0.88 microns) that were statistically significant ( p = .04); a higher number suggests less sensitivity. Hispanic women had greater changes in clitoral blood flow after sexual stimulation (38.88 ± 17.83 cm/sec vs 18.96 ± 9.36 cm/sec); however, these results were not statistically significant ( p = .0727). Conclusions: There were statistically significant differences between Hispanic and non-Hispanic women in BMI and vaginal vibratory sensations. Hispanic women experienced more personal sexual distress, had lower total testosterone levels, and had greater changes in clitoral blood flow after sexual stimulation.